Role of social responsibility on the employer's branding model in an organization - Kousar Shakeri; Karim Hamdi; Hossein Vazifehdust (Shahid Beheshti University of Medical Sciences, 2023)
Background: The main aim of this study was evaluating the role of social responsibility in the employer's branding model in the government organization of the Statistics Center of Iran. Methods: This study was applied research and a mixed method. The research tools included semi-structured interviews and researcher-made questionnaires. The statistical population in the qualitative stage included 10 experts and managers of the Statistics Center of Iran, and in the quantitative stage, it included 340 managers and staff of the Statistics Center who were selected using Cochran's formula. The data were analyzed in the qualitative section by grounded theory method using Max QUDIA software MAXQDA2020, and in the quantitative section, they were analyzed by descriptive and inferential methods using SPSS 16 and Smart PLS software. Results: In this study 340 people were analyzed. Fit tests showed that social responsibility plays an important role in the employer branding model of the Iran Statistics Center. All components with a factor load above 0.6 indicate that the model is "very desirable". Social responsibility is one of the essentials of employer branding and it is one of the important dimensions of the operational activities of organizations. The factor load of the components of "identity and credibility" was less than 0.3, these components were removed from the analysis. Conclusion: Considering the importance of social responsibility as one of the requirements of employer branding and one of the important dimensions of operational activities of organizations, managers and decision-makers should pay attention to it.